Khadija Tnana: the challenge of art in the face of the patriarchal gaze - Carratalá-Ros, Paula (Filanderas, 2022)
The artistic production of the feminist movement has helped to make visible, since the seventies, the structural and symbolic violence against women. Activist artists, through subversive and transgressive ways, seek to address the set of cultural values and religious norms that holds a whole unequal system. This paper presents the criticisms of the patriarchal order social that are developed through the artistic experiences of authors such as Khadija Tnana, intending to study the power which they burst into space for public debate to break with the expression of hegemonic masculinity. The art of this Tetouan artist, subject to patriarchal censorship, is known as an effective means of communication with which to denounce the oppression of Moroccan women, as a result of the taboos and behavioral roles that the morality of religion imposes on the female gender.